Suppression of endoplasmic reticulum stress-associated pathways and hepatocyte apoptosis participates in the attenuation of betulinic acid on alcohol-provoked liver injury in mice. Issue 22 (3rd October 2022) - He, Enqi; Ma, Yurong; Kong, Li; Huang, You; Huang, Chunlin; Yang, Wenjiang; Yi, Jine; Zhu, Lijuan
Abstract : BA protects against alcohol-induced liver damage through the alleviation of oxidative stress and suppression of ERS-induced apoptosis. Abstract : Endoplasmic reticulum stress (ERS) plays a vital role in the pathogenesis of the alcoholic liver disease (ALD). Betulinic acid (BA) has been reported to be effective in the attenuation of ALD; however, its role in ERS and associated stress-signaling pathways remains elusive. Here, we found that the BA pretreatment significantly reduced the alcohol-induced liver injury by decreasing the activities of serum alanine aminotransferase and aspartate aminotransferase, alleviating fat deposition and rupturing the ER in hepatocytes. Moreover, the protective effect of BA on ALD was associated with the inhibition of reactive oxygen species accumulation and ERS, accompanied by the downregulation of glucose-regulated protein 78 (Grp78), Grp94, phosphorylation-inositol-requiring enzyme 1α (p-IRE1α), and phosphorylation-protein kinase R-like endoplasmic reticulum kinase (p-PERK), activating the transcription factor 6 (ATF6) and C/EBP homologous protein (CHOP). Moreover, the alcohol-induced hepatocyte apoptosis was reduced, along with the downregulation of the mitogen-activated protein kinase pathway, caspase-12, caspase-3, and caspase-7, following BA administration. Additionally, the BA-mediated mitigation of alcohol-induced liver injury and deactivation of the ER pathways were the same with 4-PBA, an inhibitor of ERS, indicating that the protective effect of BA on ALD may be regulated by ERS-associated pathways. Collectively, BA is a potentially desirable agent for the ALD, which may reduce hepatocyte apoptosis by suppressing excessive ERS in the liver.